Clinical and Immunologic Predictors of Scleroderma Renal Crisis in Japanese Systemic Sclerosis Patients With Anti–RNA Polymerase III Autoantibodies. Issue 4 (April 2015) - Hamaguchi, Yasuhito; Kodera, Masanari; Matsushita, Takashi; Hasegawa, Minoru; Inaba, Yuki; Usuda, Toshikazu; Kuwana, Masataka; Takehara, Kazuhiko; Fujimoto, Manabu
Abstract : Objective: To identify predictive factors for scleroderma renal crisis (SRC) in patients with anti–RNA polymerase III (anti–RNAP III) antibodies. Methods: A total of 583 adult Japanese patients with systemic sclerosis (SSc) were screened for anti–RNAP III using a commercially available enzyme‐linked immunosorbent assay (ELISA) kit. RNAP subsets were further identified by immunoprecipitation (IP) assays. The association of clinical and immunologic factors with SRC was examined by logistic analyses. Results: In this cohort, 37 patients (6%) were positive for anti–RNAP III, as determined by anti–RNAP III–specific ELISA. Further IP assays revealed that 19 patients were positive for anti–RNAP I/III, 17 for anti–RNAP I/II/III, and 1 for anti‐RNAP III. SRC occurred in a total of 17 (2.9%) of 583 patients, with a significantly higher frequency in anti–RNAP III–positive SSc patients (9 of 37 [24%]) than those without anti–RNAP III (8 of 546 [1%]) (odds ratio [OR] 21.6 [95% confidence interval (95% CI) 7.8–60.3], P < 0.00001). Our multivariate analyses using the Cox proportional hazards regression model revealed that anti–RNAP I/II/III positivity (OR 11.0 [95% CI 1.6–222.8], P = 0.0118) and an ELISA index for anti–RNAP III of ≥157 (OR 2.4 × 10 9 [95% CI 2.1–uncalculated], P = 0.0093) were independent factors associated with the development of SRC. Conclusion: Our findings indicate that anti–RNAP III is associated with SRC, as reported previously. In addition, the presence of anti–RNAP II in combination with anti–RNAP I/III (anti–RNAP I/II/III) and a higher ELISA index for anti–RNAP III may be associated with the development of SRC in SSc patients with anti–RNAP III.